Estimating the non-market benefits of climate change adaptation of river ecosystem services: A choice experiment application in the Aoos basin, Greece. Issue 45 (January 2015) - Andreopoulos, Dimitrios; Damigos, Dimitrios; Comiti, Francesco; Fischer, Christian
Highlights: Public preferences towards climate change impacts on mountain river systems are examined. Conditional and random parameters logit and latent class models are calibrated in order to analyze trade-offs of choices and to estimate the welfare effects of climate change adaptation measures. Public's willingness to pay for climate change adaptation policies to preserve river uses is estimated. The results indicate significant benefits for main river uses preservation from climate change. Abstract: Mountains are important global reservoirs of water resources. However they are highly vulnerable to climate change as limited alterations in temperature and precipitation may cause harmful effects to water systems. Southern Europe and especially Greece are expected to undergo a drought trend over the next decades, resulting in less recharge for the aquifers and water services reduction. Thus, climate change may distort both natural and socioeconomic characteristics of freshwater ecosystem services deteriorating the general social welfare related to them. This paper examines the economic impacts of climate change on river uses of the Aoos basin in Greece. In this regard, a choice experiment is conducted to estimate the value changes in different ecological and economic services in a mountain community. The econometric simulations using conditional logit, random parameters logit and latent class models reveal that despite existing preference heterogeneity, respondents on average derive positive and significant welfare effects from climate change adaptation measures. The findings of the survey may assist in adaptation planning for the Aoos River basin, with possible extensions to other river systems enduring similar climate change indications.